2016
DOI: 10.1155/2016/6490383
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Amphiphilic Luminescent Graphene Quantum Dot and Its Application in Miniemulsion Polymerization

Abstract: Although emulsion applications of microscale graphene sheets have attracted much attention recently, nanoscale graphene platelets, namely, graphene quantum dots (GQDs), have been rarely explored in interface science. In this work, we study the interfacial behaviors and emulsion phase diagrams of hydrophobic-functionalized graphene quantum dots (C18-GQDs). Distinctive from pristine graphene quantum dots (p-GQDs), C18-GQDs show several interesting surface-active properties including high emulsification efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This phenomenon can be rationalized by the high hydrophilicity of GOQDs . Zeng et al had reported that, owing to the existence of hydrophilic carboxylic groups, the contact angle of pristine GOQD is only 14.6°, which is much lower than that of pristine TA TFC membrane in our study. Therefore, the TA/GOQDs TFN membranes with enhanced surface hydrophilicity can be obtained by increasing the GOQDs concentration in the aqueous phase.…”
Section: Resultssupporting
confidence: 84%
“…This phenomenon can be rationalized by the high hydrophilicity of GOQDs . Zeng et al had reported that, owing to the existence of hydrophilic carboxylic groups, the contact angle of pristine GOQD is only 14.6°, which is much lower than that of pristine TA TFC membrane in our study. Therefore, the TA/GOQDs TFN membranes with enhanced surface hydrophilicity can be obtained by increasing the GOQDs concentration in the aqueous phase.…”
Section: Resultssupporting
confidence: 84%
“…Overall, as shown in Figure b, the KGMF demonstrated good oil–water separation efficiency. Due to the emulsification effect of surfactant SDS, there were some oil droplets with a size too small for KGMF to interact with or withhold, though such tiny oil droplets comprised a small volume percentage of overall oil in water (Figure S4). This does lead to a slight decrease in separation efficiency as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic GQDs were produced by the thermal decomposition of CA in the presence of octadecyl amine at 200 °C for 14 min, at atmospheric pressure, and resulted in blue emission at 460 nm, at excitation of 360 nm [ 44 ]. One more procedure for the synthesis of GQDs from CA consists of its dispersion in ethanol and octadecyl amine, filtering the precipitate out of the solution, heating the mixture at 65 °C for 24 h, then adding glycine and heating the solution at 200 °C for 3 h [ 45 , 46 ]. The so-produced dots emit blue light when they are excited with UV light.…”
Section: Graphene Quantum Dots Synthetic Strategiesmentioning
confidence: 99%